Effect of Pyrolysis on shrinkage properties of SU-8 polymer - Waled Ashor M. Galy (School of Materials Engineering, University Malaysia Perlis, 2014)
Epoxy SU-8 has drawn a lot of attention during the last decades due to its promising mechanical and electrical properties. Extensive research regarding the mechanical properties of negative photoresistsSU-8 has been carried out during the last decades. A lot of effort has been put into developing methods to properly characterize features such as effect of pyrolysis temperature and the pyrolysis time on shrinkage properties and morphology of SU-8. In this workphoto patterned SU-8 were fabricated on silicon wafers by spin process for different speed steps (step (1) 250rpm and time 10sec, step (2) 450rpm and time 30sec, step (3) 0rpm and time 5sec), then Soft baked at95C for 4min before cooling for 10min.Exposure to ultraviolet (UV) light was necessary to obtain the shape of the mask, increase crosslinking degree in the irradiated areas and stabilizes them against the action of solvents during development step.